The influence of social media on employee performance: challenges and opportunities for human resources managers: a case of city of Mutare - Musara, Simbarashe (Midlands State University, 2019)
The Purpose of this study was to investigate the influence of collaborative technology such as social media influence on employee performance in the workplace. The research examines the positive and negative effects of social media on employee performance and its variables which include knowledge, skills, motivation and productivity and elaborate on the opportunities and threats for organisations that are presented by the use of social media in the workplace. The researcher was guided by the Social impact theory by Bibb (1981) and the Social media content model by JC Social Media Consultancy (2013) in coming up with a theoretic basis. The researcher used qualitative and partially quantitative approach in collecting data. The researcher focused on Mutare City council as the case study and to compliment the research the researcher used purposive sampling. The research focused on both primary and secondary data but in obtaining information from respondents mainly primary data was used through research instruments such as structured interviews, questionnaires. Mutare City Council had a workforce of 1200 at the time the research was conducted and this was the sample frame of the researcher and a small sample size of 60 people was selected including the top management, middle management and the shop floor workers. Of the 60 selected only 41 took part in the research. The findings revealed that there is rampant use of social media and with its addictive nature it slowing down the production and service provision process as attention of employees is lost through the use of social media. It was also discovered that social media was now an integral part of society and Human Resource managers have to embrace it’s use and try to mitigate its challenges whilst at the same time improving the performance of employees through social media tools. From the research findings, the researcher recommended that the organisation should craft a social media policy, monitor social media, educate employees on the pitfalls of social media and embrace the use of social media. The conclusion made was that at the workplace social media is a necessary evil and Human Resources managers should embrace it with all its challenges that are performance related and some which are not and try to use it to positive use for the organisation.